Mechanism-based intervention in Non-Alcoholic Fatty Liver Disease: mapping the muscle-liver axis and exploring the effect of L-carnitine on liver fat, insulin sensitivity and mitochondrial energy kinetics - Thiagarajan, Prarthana (2021)
The rising prevalence of non-communicable disease reflects a global healthcare burden that is the product of overnutrition and physical inactivity. As these deleterious lifestyles persist, their metabolic consequences have reached epidemic proportions. In this context, and with its corollaries of obesity and insulin resistance, non-alcoholic fatty liver disease (NAFLD) presents a growing public health and economic challenge. With no approved pharmacological treatment currently available, NAFLD will dominate the landscape of hepatology for the foreseeable future. Its prevalence, associated complications and escalation of disease burden in coming decades together underscore a time-critical unmet need for disease-modifying therapy which is broadly applicable, safe and cost-effective.